Upaya Dinas Tenaga Kerja Dalam Mengurangi Konflik Ketenagakerjaan Di Kota Surabaya - Trisindra Amilia Cahyani Putri; Ismail; Tri Prasetijowati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2024)
This study aims to determine how the Manpower Office's efforts in reducing labor conflicts in the city of Surabaya and to analyze the obstacles and barriers experienced by the Manpower Office in making its efforts to reduce existing labor conflicts. The focus of the problem in this study is (1) Efforts of the Manpower Office in reducing labor conflicts in the city of Surabaya (2) Supporting and Inhibiting Factors of the Manpower Office in reducing Labor Conflicts in the city of Surabaya. The type of research uses a descriptive method. The data collection method used is the interview method, and the documentation method and the data used in this study are primary data and secondary data. While the research approach used is Qualitative research. In analyzing the data, the author uses data reduction, data presentation and drawing conclusions from the data. The results of this study indicate that the Surabaya City Manpower Office has tried and made various efforts to reduce labor conflicts but there are still various obstacles faced such as (1) lack of coordination between institutions (2) Low awareness of labor regulations (3) Weak law enforcement. Employment Conflicts have yet to show a significant decline. More Comprehensive and Sustainable Efforts are needed from all relevant parties to resolve this problem completely